Making Sense of Work Through Collaborative Storytelling Building Narratives in Organisational Change - Cleland Silva, Tricia (Springer Nature, 2022)
Collective sense making starts with individual stories. Stories influence how we construct our sense of self in relation to others and our social environment, especially within the world of work. The stories we tell ourselves at work, particularly during times of change, impact our relationships and the collaboration with those who are engaged in the same work activities. Stories that we take for granted as "common sense" may not resonate with others, leading to conflict and tensions. This book focuses on the development of collaborative practices at work, and in organisations, through Collaborative Storytelling: from sharing stories to exchanging experiences and building a common narrative collectively. This open access book will be of interest to practitioners and academics working in the fields of adult education, equity and inclusion, human resource management, practice-based studies, organisational studies, qualitative research methods, sensemaking, storytelling, and workplace identity.